Do business cycle conditions at the time of labour market entry affect future unemployment? - Oddbjørn Raaum; Knut Røed (University of Oslo, Department of Economics, 2002)
Labour market conditions at the time and place of potential entry into the labour market are shown to have a substantial and persistent impact on adult labour market performance. Birth cohorts that face particularly depressed labour markets when they graduate from primary- and/or secondary education are – other things equal - subject to relatively high rates of unemployment during their whole prime-age work career. Building on a unique combination of micro- and macro data from Norway, we show that these effects are robust with respect to model-specifications and conditioning variables, and that they are not limited to particularly disadvantaged groups of workers.
Keywords: J64; 330; Unemployment; Marginalisation; Scarring; Arbeitslosigkeit; Arbeitsmarkt; Konjunktur; Erwerbsverlauf; Zeitreihenanalyse; Norwegen